Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Electrochemical polymerization of o-anisidine on low carbon steel from aqueous salicylate solution: corrosion protection study - Wankhede, M. G.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
The electrochemical polymerization of o-anisidine was carried out on low carbon steel from an aqueous salicylate medium using cyclic voltammetry. The resulting poly(o-anisidine) coatings were uniform and adherent to the steel substrates. These coatings were characterized by cyclic voltammetry, LTV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction measurements and scanning electron microscopy. The ability of the poly(o-anisidine) coatings to protect low carbon steel in an aqueous 3% NaCl was evaluated by the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(o-anisidine) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; low carbon steel; poly(o-anisidine) coatings

Electrochemical synthesis of corrosion protective polyaniline coatings on mild steel from aqueous salicylate medium - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Science and Technology of Advanced Materials, 2006)
Strongly adherent polyaniline coatings were electrochemically synthesized on mild steel from an aqueous salicylate medium. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The extent of the corrosion protection offered by polyaniline coatings to mild steel was investigated in aqueous 3% NaCl solution, 0.01 M Na2SO4 Solution and in aqueous solutions of NaCl + Na2SO4 with different concentrations by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies reveal that the corrosion resistance of the polyaniline-coated mild steel is significantly higher and the corrosion rate is considerably lower than that of uncoated steel. (c) 2006 Published by NIMS and Elsevier Ltd.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; polyaniline coatings mild steel

Electrical behavior of silver particulate films deposited on 8 MeV electron beam irradiated softened polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Journal of Materials Science-Materials in Electronics, 2011)
Results of the investigations carried out on the electrical behavior of silver particulate films deposited on electron beam irradiated polystyrene (PS) coated substrates held at a temperature of 455 K in a vacuum of 8 x 10(-6) torr at a constant deposition rate of 0.4 nm/s are reported. It is known that when metals are evaporated on to softened polymer substrates, subsurface particulate structures are formed whose morphology is dependent on deposition parameters. Further, it was shown that the morphology is dependent on polymer-metal interaction. The present work demonstrates that the polymer-metal interaction can be brought about in inert polymers like PS by electron irradiation. The results indicate that the films deposited on PS irradiated to a dose of 20 and 25 kGy gives rise to smaller clusters with smaller inter-cluster separation, better suited for sensor applications. The induced polymer-metal interaction is attributed to the creation of free radicals due to the 8 MeV electron irradiation.